2019
DOI: 10.1109/tmi.2018.2865659
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Plaque Detection in IVOCT Pullbacks Using Convolutional Neural Networks

Abstract: Coronary heart disease is a common cause of death despite being preventable. To treat the underlying plaque deposits in the arterial walls, intravascular optical coherence tomography can be used by experts to detect and characterize the lesions. In clinical routine, hundreds of images are acquired for each patient which requires automatic plaque detection for fast and accurate decision support. So far, automatic approaches rely on classic machine learning methods and deep learning solutions have rarely been st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 41 publications
1
70
0
1
Order By: Relevance
“…When it comes to plaques detection in IOCT, the survey of Boi et al [8] describes that methods using texture information for plaque detection and classification performs with accuracy ranging between 80.41% and 88%. The recent paper of Gessert et al [6] report an accuracy of 92% for plaque detection using texture information. It is interesting to notice that our method, that takes into account only the lumen geometry was able to achieve 91% of accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to plaques detection in IOCT, the survey of Boi et al [8] describes that methods using texture information for plaque detection and classification performs with accuracy ranging between 80.41% and 88%. The recent paper of Gessert et al [6] report an accuracy of 92% for plaque detection using texture information. It is interesting to notice that our method, that takes into account only the lumen geometry was able to achieve 91% of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers address atherosclerotic plaques classification in IOCT through the analysis of 2D slices of the vascular wall and propose methods usually very related to texture pattern recognition [3,4]. For instance, Athanasiou et al [5] used Random Forest to analyze textures and classify different plaques and [6] proposed a method to detect and classify plaques between calcified and fibrous/lipid using deep learning model, such as Resnet50 and Densenet-121. Macedo et al [7] proposed to identify side branches in slices using only the lumen contour and reported that irregular geometry in slices with plaque was the main cause of confusion since regular slices without plaques present a nearly circular lumen shape.…”
Section: Introductionmentioning
confidence: 99%
“…The features vectors for classification consist of light attenuation coefficients and textures based on gray level co‐occurrence matrix in vessel layer. Gessert et al used convolutional neural networks (CNNs) as a machine learning algorithm to classify plaque using IVOCT images. However, the size of dataset and the number of expert consultants for IVOCT image assessment were small for further plaque detection.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, we investigate both the differentiability of organs and also of malignant and non-malignant tissue both for the colon and peritoneum. As we are dealing with a very small dataset we employ transfer learning which has been shown to improve performance for a variety of medical learning problems [6,7]. We use the state-of-the-art models Densenet121 [8] and SE-Resnext50 [9] which are pretrained on the ImageNet dataset.…”
Section: Introductionmentioning
confidence: 99%